The issues and challenges of halal foods certification in Malaysia / Afzan Basir, Rafidah Shahrul and Suhaimi Saad - Basir, Afzan; Shahrul, Rafidah; Saad, Suhaimi (2006)
Everyday, we are exposed with various issues relating to Halal foods. In the newspapers and electronic media, lot of issue has been revealed regarding Halal certification. It include the misuse of Halal certification, logo misuse, Halal food being mixed with non- Halal food, animals improperly slaughtered according to Syara' but is Halal, the processed food mixed with non- Halal ingredients and others. There are shops and restaurants which put the Halal word, the Quranic verses or employed Malay or Indonesian workers to convince that the products is Halal, but the fact is that the person who runs the business is non- Muslim. The question is how we can avoid this matter in order to maintain the Muslim aqidah which are closely related to the spiritual aspect of Islam